Unusual lattice vibration characteristics in whiskers of the pseudo-one-dimensional titanium trisulfide TiS3 - Kedi Wu (Nature Portfolio, 2016)
Transition metal trichalcogenides are layered materials with strong in-plane anisotropy, and their vibrational characteristics remain largely unexplored. Here, the authors present high-pressure Raman studies to uncover unusual vibrational effects within this specific class of materials.